2015
DOI: 10.1088/0268-1242/30/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent electro-thermal simulations of AlGaN/GaN diodes by means of Monte Carlo method

Abstract: In this contribution we present the results from the simulation of an AlGaN/GaN heterostructure diode by means of a Monte Carlo tool where thermal effects have been included. Two techniques are investigated: (i) a thermal resistance method (TRM), and (ii) an advanced electro-thermal model (ETM) including the solution of the steady-state heat diffusion equation. Initially, a systematic study at constant temperature is performed in order to calibrate the electronic model. Once this task is performed, the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…This is due to the shift of the V GS to higher values in SiC, leading to higher dissipated power. We have found that T av is linear with respect to the dissipated power, so that we can extract the slope of this linear fitting and define an equivalent thermal resistance R th as shown in [16]. In figure 4(a) 4(a)) we obtain the same transfer characteristics and transconductance as those provided by the HDEM, as can be seen by the solid lines of figures 2(a) and (b).…”
Section: Substrate Effectmentioning
confidence: 66%
See 1 more Smart Citation
“…This is due to the shift of the V GS to higher values in SiC, leading to higher dissipated power. We have found that T av is linear with respect to the dissipated power, so that we can extract the slope of this linear fitting and define an equivalent thermal resistance R th as shown in [16]. In figure 4(a) 4(a)) we obtain the same transfer characteristics and transconductance as those provided by the HDEM, as can be seen by the solid lines of figures 2(a) and (b).…”
Section: Substrate Effectmentioning
confidence: 66%
“…The simulation method used in this paper (heat diffusion equation model, HDEM) iteratively couples the MC electronic transport with the solution of the steady-state heat-diffusion equation (HDE) [16] (where radiation and convection losses are neglected): where T(r) and G(r) are the temperature and the dissipated power density, respectively, at position r, and k(r, T) is the temperature-dependent and inhomogeneous thermal conductivity. The thermal domain (region where the HDEM is applied), covers the whole device and is delimited by green dashed lines in figure 1.…”
Section: Device Details and Simulation Methodsmentioning
confidence: 99%
“…AlN 170 We perform the simulations with the heat-sink 8 at a temperature T = 300 K and the thermal conductivities of Table 3.3. In [36] it was argued that both models, TRM and ETM, are equivalent because the current is determined by the average temperature (T av ) inside the device, which is very similar with both models. Note that in the TRM the temperature is uniform, but in the ETM it changes from mesh to mesh.…”
Section: Room Temperature Operationmentioning
confidence: 97%
“…There are both commercial and home-made simulators that can deal with thermal eects. Dierent models have been suggested like the thermal resistance approach [36], the solution of the steady-state heat conduction equation self-consistently with the microscopic transport in the device [37,38], or models based on analytical formulations [39,40].…”
Section: Gan-based Detectorsmentioning
confidence: 99%
See 1 more Smart Citation